EFFECT OF MINOR ALLOYING ADDITION ON PROPERTIES OF Zr-BASED BULK METALLIC GLASS - Iqbal, M.; Akhtar, J. I. (The Nucleus, 2010)
An alloy with composition Zr64Ni17Al11.5Cu7.5 was designed using the criterion of valence electron-atom ratio (1.38) and average atomic size Ra (0.1498 nm). Addition of 2 at. % Ti, V and Pd was carried out in the base alloy. All the alloys were synthesized by Cu mold casting and characterized by SEM, EDS, FESEM, DSC and XRD techniques. Effect of additives on mechanical and thermal properties was studied. The alloys showed good mechanical properties. All the alloys have high fracture strength. Improvement in ductility was achieved with the elemental addition of Ti and V which produced intersecting shear bands in the alloy during compression tests. The calculated thermal parameters indicate good glass-forming ability (GFA) and high thermal stability. Nucleation of liquid droplets within the vein patterns verifies the adiabatic heating theory of BMGs